Not all physical performance tests are related to early season match running performance in professional rugby league - Glassbrook, D. J.; Fuller, J. T.; Wade, J. A.; Doyle, T. L. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to determine which physical tests correlate with early season running performance. Sixteen professional rugby league players performed the 30-15 intermittent fitness test (IFT), 1.2-km time trial, 1 repetition maximum (RM) barbell back squat, isometric midthigh pull (IMTP), countermovement jump (CMJ), barbell squat jump (SJ), and ballistic bench press throw (BBP). Bivariate Pearson's correlations and linear regression were used to compare physical tests with peak match running intensities recorded by a portable Global Positioning System and represented by peak match velocity and acceleration, as well as peak 1-, 4-, 6-, and 8-minute instantaneous acceleration/deceleration periods of play. Significant (p < 0.05) negative correlations (r = -0.55 to -0.60) were observed between the IFT and relative 1-, 4-, 6-, and 8-minute peaks, and between the relative 1RM back squat and relative 1-, 4-, 6-, and 8-minute peaks. Significant positive correlations (r = 0.52-0.84) were observed between the following physical tests and match performance pairs: IFT and peak acceleration; relative 1RM back squat and peak acceleration; SJ peak power (relative and absolute) and peak acceleration; CMJ peak force (relative and absolute) and peak acceleration; CMJ peak power (relative and absolute) and peak acceleration and 1-, 4-, 6-, and 8-minute peaks; and relative BBP peak power and peak velocity and peak acceleration. The results of this study highlight that not all generic tests of physical qualities are related to peak match running performance and only those with significant correlations are likely to be able to indicate how players may perform during match-play.